Registration-based transfer listing system and high-tech SME innovation: Research on China’s specialized and sophisticated SMEs listed on the National Equities Exchange and Quotations. - Junjie Du; Dong Lu (PLoS ONE, 2025)
In China, high-tech small and medium-sized enterprises (SMEs) are a crucial component of the innovation ecosystem, and how to effectively promote innovation within these firms has become a pressing challenge for the government. Against the backdrop of the registration-based reform, we use a sample of specialized and sophisticated SMEs listed on the National Equities Exchange and Quotations (NEEQ) from 2016 to 2022 to empirically examine the impact of the registration-based transfer listing system (RTLS) on the innovation activities of NEEQ high-tech SMEs. We find that RTLS can enhance innovation input by improving stock liquidity. Meanwhile, we find that RTLS can also promote substantive innovation output by strengthening information disclosure. We further document that the positive effect is more pronounced in highly marketized regions and among non-state-owned enterprises. Further analysis shows that RTLS can enhance innovation efficiency and lessen reliance on fiscal subsidies to promote innovation for NEEQ high-tech SMEs.